Implementation of a Custom Muon High Level Trigger Monitoring System - Mohlalisi, Seforo (Department of Physics, 2014)
A Large Ion Collider Experiment (ALICE) is one of the 4 major experiments at the Large Hadron Collider (LHC) at CERN. Its main aim is to investigate the physics of strongly interacting matter in proton-proton, nucleus-nucleus and nucleus-proton or proton-nucleus collisions at ultra high energy densi- ties, where the Quark Gluon Plasma (QGP) is expected to form. The experiment is expected to produce data at very high rates of about 25 Gbytes/s however the bandwidth to permanent storage is limited to about 10% (1.25 Gbyte/s) of the total expected data rates. In order to reduce data to permanent storage a special level of selecting interesting/relevant physics events is required. In ALICE the trigger (selection) of signals is issued based on a series of levels varying from levels 0 (L0) up to the High Level Trigger (HLT). For the ALICE muon spectrometer, the role of the trigger is to select events containing muon tracks, with the transverse momentum (pt) above a given threshold. Due to the limited spatial resolution of the muon trigger chambers a pt cut above a few GeV with the L0 trigger is not possible. While the L0 signal for the muon spectrometer is issued at about 700 - 800 ns, the HLT is delivered at about 1 ms. The role of the HLT is to perform online and o ine reconstruction of the ALICE muon spectrometer data in order to improve the measured (L0) pT resolution. In this way a better separation between relevant physics events and unwanted events (background) can be attainable, which could eventu- ally lead to lower trigger rates. The HLT is designed to improve signal- to-background ratio in the raw data transferred to the storage. In order to facilitate online/o ine data analysis the HLT monitoring system which will enable the user to graphically view the events during the reconstruc- tion phase was developed in this study. The system will read and decode the reconstructed events from the HLT analysis chain using the HLT Online Monitoring Environment including ROOT (HOMER) and displaying them on the ALICE Event Visualization Environment (ALIEVE). In addition, the ii utility, dHLTdumpraw, that inspects, with ner detail, the contents of all muon HLT internal data blocks and the detector data link (DDL) raw data stream is also described.